Governance Networks for Effective Custodians’ Participation in the Sustainability of Langkawi as a Geopark - Geraldine K. L. Chan (Kajian Malaysia, 2017)
The Global Geopark Networks (GGN) created the concept of "geopark" as a geographically designated area that contains geological, ecological, historical cultural resources for community sustainable development primarily through tourism activities. The Langkawi archipelago has always been rich in such resources and heritage, and was conferred the geopark status by GGN in 2007. Since then, the government and some private, non-governmental organisations have been involved in many geopark projects and activities. Some of them are members of the top down governance system while other parties work independently of one another. For Langkawi to sustain in the long run as a successful and economically developed geopark without the depletion of its geological, ecological, cultural and historical resources, its governance system can be further improved. Effective custodian participation is best achieved through proper governance network system whereby the networks are established between at least two or more organisational and non-organisational custodians irrespective of their social status, ethnicity, gender, wealth and income levels. Specifically, the custodians should work closely together and establish networks in a transparent, accountable, responsible, fair, trustworthy and consistent manner. Effective participation should be in terms of shared norms of behaviour such as cooperation, assistance and influence. Furthermore, such effective participation is based on shared views, shared values, shared norms and other shared aspects guided to some extend by basic network principles such as reciprocity and mutuality. This implies that similarity or commonality is a key feature in social networks formation of the custodians. Trust is also present as a network element. For Langkawi to sustain as a geopark in present and future times, effective participation from all custodians can be achieved through governance networks or social networks. This paper will present some findings from two empirical studies conducted on effective governance networks for the success of Langkawi as a geopark.